Edukasi Gizi Seimbang pada Anak sebagai Upaya Pencegahan dan Penurunan Stunting di RW 03, Kelurahan Pulo Gebang, Kecamatan Jakarta Timur - Dian Marlina, Endah; Raudhatul Munawarah; Istianaah Wahyuningsih (PPNI UNIMMAN, 2025)
Stunting is a growth and development disorder in children caused by chronic malnutrition, repeated infections, and lack of psychosocial stimulation. It remains a major public health issue in Indonesia, which ranks second in Southeast Asia for stunting prevalence among toddlers. According to the Asian Development Bank (ADB), the prevalence was 31.8% in 2020. Although declining, the national prevalence remained high: 30.8% in 2018, 27.7% in 2019, 24.4% in 2021, and 21.6% in 2022. These figures still exceed the World Health Organization’s (WHO) maximum threshold of 20%. The Indonesian government aims to reduce the prevalence to 14% by 2024.One key intervention to address stunting is balanced nutrition education for children and their caregivers. This educational approach targets mothers and local health cadres to increase awareness of adequate and quality nutrition for child development. Community empowerment plays a vital role in this effort, particularly in enabling early detection and response to stunting risks.To support this, a Community Service initiative was implemented through a program by the Midwifery Department at Poltekkes Kemenkes Jakarta III. The team developed and provided educational media to assist communities in understanding and applying good nutrition practices, thereby contributing to stunting prevention at the grassroots level.